The Problem with Problems: Fundamental to Applied Research Using Palladium - Watson, Allan J. B. (Synlett, 2020)
This Account describes the development of our cross-coupling and medicinal chemistry research from its origins at the outset of my independent career through to the present day. Throughout, the decisions and motivations as well as the mistakes and pitfalls are discussed.1 Introduction2 Hobbies and Interests3 Scooped before Starting4 Opportunity from Collaboration5 Chemoselective Suzuki–Miyaura Cross-Coupling6 Applications to the Medicinal Chemistry Campaign7 Autotaxin and Heterocycle Synthesis8 ATX Hybrids and Pd(II) Speciation9 Conclusions
Keywords: boron; cross-coupling; medicinal chemistry; palladium; speciation